Effectiveness of a Support-Training Program based on the Orem's Self-Care Deficit Theory on the Quality of Life of Children Undergoing Hemodialysis - Fahimeh Khazaei; Naghmeh Razaghi; Hamidreza Behnam Vashani (Mashhad University of Medical Sciences, 2021)
Background: Most children undergoing hemodialysis (HD) are burdened with some deficits to practice self-care, causing poor quality of life (QoL). Orem's Self-Care Theory (SCT) is known as one of the nursing models involving patients in care and putting much more emphasis on self-care. Aim: This study aimed to investigate the effectiveness of a support-training program developed based on Orem's SCT on QoL among Iranian children undergoing HD. Method: This quasi-experimental study with a pretest-posttest research design was conducted using the census method on a total number of 27 children aged 8-15 undergoing HD at Dr. Sheikh Hospital, Mashhad, Iran, in 2019. For this purpose, the Self-Care Measurement Scale (Shintani, 2009) and the KIDSCREEN-52 quality of life questionnaires were completed before the inclusion of the study participants, and then, universal self-care and health-deviation self-care needs were identified. The data were further analyzed in the SPSS Statistics software (version 16). Results: The total mean scores of QoL were obtained at 24.9±0.118 and 27.3±0.177 before and immediately after the intervention program, respectively. The results of the Bonferroni posthoc test showed a significant difference between the total mean scores of the pretest-posttest stages (P˂0.001). Moreover, the difference between the total mean scores was significant 2 and 6 weeks after the implementation of the given program and immediately after it (P˂0.001). Implications for Practice: Since, in this study, the self-care support-training program practiced was developed based on Orem's SCDT, the study findings can be utilized in planning to improve the QoL of children undergoing HD.